Identifying design deficiencies through anaesthetic incidents - Sellen, Abigail; Senders, J. W.; Russell, J. (Trans. on Multi-Disciplinary Engineering, Australia, 1998)
Detailed analysis of a sample of 261 anaesthetic incidents showed that almost half of them were associated with weaknesses in engineering design. Many of these incidents may have been avoided if a defensive approach were taken to the design or manufacture of the anaesthetist's equipment or environment. Feedback from incident reporting is an effective way to probe the weaknesses of the present anaesthetic management and give a guide to how to achieve improvement.